Heurística matemática para resposta emergencial no sistema de distribuição de energia elétrica com ilhamento imprevisto - Schmitz, Magdiel (2018)
The main objective of the electric power utility is the uninterrupted supply of energy, however, this is not always possible due to the actions of nature, or even from equipment or human failures. These interruptions are called emergency orders, which must be serviced by repair crew in order to restore normal operation of the electrical system. Given a set of emergency orders, the operations center must find a crew scheduling in order to attend all orders and minimize the total cost of service. Before the system repair step, the restoration step is performed, in order to supply the de-energized loads belonging to the healthy parts of the network. One of the ways to supply them is through distributed generation (DG), such as solar and wind, with high penetration in the electric system in recent years, operating in islanded mode. The island operation plays an important role in the restoration step of the electric power system, as it allows to reduce the total interruption time. It allows analyzing the impact of customer cost, with interrupted power supply, depending on the time of day, varying with the capacity of the DG generation curve and the load curve. In this way, this work proposes a new matheuristic for emergency response for the emergency orders scheduling problem (EOSP) of the electric distribution systems, considering unforeseen islanding. The model has the objective of minimizing the total attendance cost, being for this model the costs of energy not supplied and those related to the penalties, associated to the importance of consumers. The matheuristic will serve as a management tool for decision-makers to determine an appropriate scheduling strategy. In this work the computational implementation of the proposed model is presented, with the realization of two case studies in the IEEE 33-bus system, modified with DGs insertion. Computational results show the effectiveness of the model developed by reducing the total attendance cost in relation to the case without islanding and the feasibility for applications in other distribution systems.